Investigating the impact of sleep quality on cognitive functions among students in Tokyo, Japan, and London, UK - Ampofo, Joshua; Sun, Binghai; Bentum-Micah, Geoffrey; Qinggong, Li; Changfeng, Wang; Guoan, Le; Xusheng, Qian (Frontiers in Sleep, 2025)
BackgroundThis study focuses on cultural influences and investigates sleep quality's impact on cognitive functions among university students in Tokyo and London. Recognizing sleep as vital for wellbeing and academic success, it explores factors affecting sleep quality and its cognitive impact in diverse educational settings.MethodsA cross-sectional study was conducted with 400 students (200 per city). The Pittsburgh Sleep Quality Index (PSQI) assesses sleep quality. At the same time, cognitive tests, including the Rey Auditory Verbal Learning Test and the Stroop Test, evaluated memory, attention, problem-solving, and executive functions.ResultsSignificant negative correlations emerged between PSQI scores and cognitive performance, indicating that poorer sleep quality correlated with diminished cognitive abilities across domains. Regression analyses confirmed sleep quality's predictive role in mental performance, controlling for demographics. These findings highlight sleep's critical role in cognitive functions within different cultural contexts.ConclusionThis study underscores sleep quality's importance for academic success and reveals cultural variations influencing sleep patterns among Tokyo and London students. The findings suggest targeted interventions to enhance sleep quality and cognitive functioning in diverse educational settings, considering cultural nuances and lifestyle factors. Further research should explore longitudinal effects and intervention strategies to improve sleep and mental outcomes.